Kontestasi Dewan Perwakilan Rakyat dan Mahkamah Konstitusi dalam Menyelesaikan Polemik Lembaga Penyelenggara Pemilu di Aceh - Karim, Zahlul Pasha; Akbar, Khairil; Makinara, Ihdi Karim (De Jure: Jurnal Hukum dan Syari'ah, 2021)
Abstract: This article tries to trace the steps of the House of Representatives which revoked two articles in Law Number 11 of 2006 concerning Aceh Governance, namely Article 57 and Article 60 paragraph (1), (2) and (4), which relate to the Aceh election institution through Law Number 7 of 2017 concerning General Elections. Later, the Constitutional Court's action was annulled by the Constitutional Court because it violated the formal procedure for amending the Aceh Governance Law. The research method was carried out normatively with two problem formulations, why did the House of Representative revoke two articles of the Aceh Governance Law related to election management institutions in Aceh without complying with and even violating the procedures regulated by the Aceh Governance Law as a special law? Why did the Constitutional Court annulled the revocation of the two articles and consider them unconstitutional? The result showed that the revocation of the two articles was carried out by the House of Representative for several reasons, namely removing the dualism of the election supervisory agency in Aceh and tidying up the structure of the election management body in Indonesia to comply with the provisions of Article 22E paragraph (5) of the Constitution of the Republic of Indonesia. In 1945 and strengthening election administration institutions in the face of simultaneous elections in 2019. Meanwhile, the steps were taken by the Constitutional Court to cancel the revocation of the two articles and judge them as unconstitutional because the House of Representative did not conduct consultations and asked the Aceh People's Representative Council for consideration in the revocation process.Keywords: Aceh Election Commission; Election Supervisory Committee; Aceh Governance Law; Election Law.Abstrak: Artikel ini bertujuan menelusuri langkah DPR yang mencabut dua pasal dalam Undang-Undang Nomor 11 Tahun 2006 tentang Pemerintahan Aceh (UUPA), yakni Pasal 57 dan Pasal 60 ayat (1), (2) dan (4), yang berhubungan dengan lembaga penyelenggara pemilu di Aceh melalui Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum. Belakangan, pencabutan itu dibatalkan oleh Mahkamah Konstitusi karena dinilai inkonstitusional. Metode penelitian dilakukan secara normatif dengan dua rumusan masalah, mengapa DPR mencabut dua pasal UUPA terkait lembaga penyelenggara pemilu di Aceh tanpa mematuhi tata cara yang telah diatur oleh UUPA sebagai undang-undang khusus? Mengapa Mahkamah Konstitusi membatalkan pencabutan kedua pasal tersebut dan menilainya sebagai tindakan inkonstitusional? Adapun metode penelitian adalah hukum normatif dengan pendekatan perundang-undangan, teori, dan historis. Hasilnya diperoleh bahwa pencabutan kedua pasal tersebut dilakukan DPR karena beberapa alasan, yakni menghapus dualisme lembaga pengawas pemilu di Aceh dan menertibkan struktur lembaga penyelenggara pemilu di Indonesia agar sesuai dengan ketentuan Pasal 22E ayat (5) Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Sementara langkah Mahkamah Konstitusi membatalkan pencabutan kedua pasal tersebut dan menilainya sebagai tindakan inkonstitusional dikarenakan DPR tidak melakukan konsultasi dan meminta pertimbangan DPRA dalam proses pencabutan.Kata Kunci: Dewan Perwakilan Rakyat; Mahkamah Konstitusi; Lembaga Pemilu Aceh; Undang-undang Pemilu.